From the first equation,
x+5 = 3(y+5)
x = 3y + 15 - 5
Now substitue x in the second equation with (3y +15 - 5).
x-5 = 7(y-5)
(3y+15-5) - 5 = 7(y-5)
3y +5 = 7y - 35
-4y = - 40
y = 10
Since y is 10, and x is (3y +15 - 5),
x = 30 + 15 - 5 = 40
Answer: <span>2x² + x - 2 (the first option)</span>
Answer:
$134,061.09
Step-by-step explanation:
hope this helps
Answer:
he gets 4.33 dollars back
Step-by-step explanation:
add 2.75+1.20+1.35+0.37= 5.67
10-5.67=4.33 $
In a way, you are adding like terms.
3.5 + 2.7 = 6.2, therefore making the answer 6.2 + x
The brackets can be ignored so you are really just asked 8 x 4 x k. 8 x 4 =32 so you end up with 32k